Perspectives of key stakeholders on employment of autistic adults across the United States, Australia, and Sweden - Black, Melissa; Mahdi, S.; Milbourn, Ben; Thompson, Craig; D'Angelo, A.; Ström, E.; Falkmer, Marita; Falkmer, Torbjorn; Lerner, M.; Halladay, A.; Gerber, A.; Esposito, C.; et al. (WILEY, 2019)
© 2019 International Society for Autism Research, Wiley Periodicals, Inc.